Organic Condensation and Particle Growth to CCN Sizes in the Summertime Marine Arctic Is Driven by Materials More Semivolatile Than at Continental Sites. Issue 20 (21st October 2017) - Burkart, Julia; Hodshire, Anna L.; Mungall, Emma L.; Pierce, Jeffrey R.; Collins, Douglas B.; Ladino, Luis A.; Lee, Alex K. Y.; Irish, Victoria; Wentzell, Jeremy J. B.; Liggio, John; Papakyriakou, Tim; Murphy, Jennifer; et al.
Abstract: Ship‐based aerosol measurements in the summertime Arctic indicate elevated concentrations of ultrafine particles with occasional growth to cloud condensation nuclei (CCN) sizes. Focusing on one episode with two continuously growing modes, growth occurs faster for a large, preexisting mode (dp ≈ 90 nm) than for a smaller nucleation mode (dp ≈ 20 nm). We use microphysical modeling to show that growth is largely via organic condensation. Unlike results for midlatitude forested regions, most of these condensing species behave as semivolatile organics, as lower volatility organics would lead to faster growth of the smaller mode. The magnitude of the CCN hygroscopicity parameter for the growing particles, 0.1, is also consistent with organic species constituting a large fraction of the particle composition. Mixing ratios of common aerosol growth precursors, such as isoprene and sulfur dioxide, are not elevated during the episode, indicating that an unidentified aerosol growth precursor is present in this high‐latitude marine environment. Key Points: A particle formation and growth event in the marine Arctic was observed leading to enhanced numbers of cloud condensation nuclei Microphysical modeling and hygroscopicity measurements show that growth is governed by organic species of unknown origin The condensing gas‐phase material is surprisingly semivolatile, whereas less volatile material condenses at continental, lower latitude sites